Metabolic requirements of CD160 expressing memory‐like NK cells in Gram‐negative bacterial infection - Anucha Preechanukul; Natnaree Saiprom; Kitilak Rochaikun; Boonthanom Moonmueangsan; Rungnapa Phunpang; Orawan Ottiwet; Yuphin Kongphrai; Soonthon Wapee; Rachan Janon; Susanna Dunachie; Barbara Kronsteiner; Narisara Chantratita (Clinical & Translational Immunology, 2024)
Abstract Objective Unique metabolic requirements accompany the development and functional fates of immune cells. How cellular metabolism is important in natural killer (NK) cells and their memory‐like differentiation in bacterial infections remains elusive. Methods Here, we utilise our established NK cell memory assay to investigate the metabolic requirement for memory‐like NK cell formation and function in response to the Gram‐negative intracellular bacteria Burkholderia pseudomallei (BP), the causative agent of melioidosis. Results We demonstrate that CD160+ memory‐like NK cells upon BP stimulation upregulate glucose and amino acid transporters in a cohort of recovered melioidosis patients which is maintained at least 3‐month post‐hospital admission. Using an in vitro assay, human BP‐specific CD160+ memory‐like NK cells show metabolic priming including increased expression of glucose and amino acid transporters with elevated glucose uptake, increased mTOR activation and mitochondrial membrane potential upon BP re‐stimulation. Antigen‐specific and cytokine‐induced IFN‐γ production of this memory‐like NK cell subset are highly dependent on oxidative phosphorylation (OXPHOS) with some dependency on glycolysis, whereas the formation of CD160+ memory‐like NK cells in vitro is dependent on fatty acid oxidation and OXPHOS and further increased by metformin. Conclusion This study reveals the link between metabolism and cellular function of memory‐like NK cells, which can be exploited for vaccine design and for monitoring protection against Gram‐negative bacterial infection.